Multispecific antibodies: Bioanalytics for early-stage screening and characterization of mispairing profiles - Catarina Melo; Sofia B. Carvalho; Maria J. Sebastião; Ricardo A. Gomes; Pedro M. F. Sousa; Patrícia Gomes-Alves (PLoS ONE, 2025)
Multispecific antibodies (MsAbs) enable the targeting of different epitopes, representing a strategy with enhanced therapeutic potential. However, the intracellular assembly of MsAbs is complex and generates unwanted mispaired species, imposing a significant burden on downstream processing and analytical characterization, thus increasing the overall timeline and cost of bioprocess development. The establishment of analytical tools to aid in the characterization and understanding of MsAb mispairing profiles at early-stage screenings is mandatory. Here, we implemented mass spectrometry (MS) and high-performance liquid chromatography (HPLC) methods to assess mispairing levels using several Chinese Hamster Ovary (CHO) clones producing a MsAb. Results showed that both methods are suitable to be explored in early-stage screenings enabling the identification of higher quality MsAb producer clones. Importantly, not only protein A-purified but also clarified samples can be analysed by the methods established, streamlining the characterization process and reducing costs and analysis time. Moreover, we evaluated the impact of different mispairing levels on antibody functionality by biophysical tools. Nano-Differential Scanning Fluorometry (nDSF) was used to record thermal stability profiles and Surface Plasmon Resonance (SPR) to infer on the binary interactions established with three different antigens, revealing distinct profiles between groups with higher and lower mispairing levels. Our work allowed the development and implementation of a mispairing analytical toolbox, critical for early-stage screening and deeper characterization of these complex biopharmaceuticals.